Nikelj kot pomemben element v sledovih? - Košak, Urban (Farmacevtski vestnik, 2012)
Nickel is a transition metal that cycles through redox states 0, +1, +2 and +3in biochemical processes. The role of nickel in humans and animals is not completely understood due to the lack of knowledge of enzymes or cofactors that include nickel. In microorganisms eight nickelcontaining enzymes are known. These enzymes are essential not only to the microorganisms but also to other organisms. From a pharmaceutical standpoint urease is the most important nickel-containing enzyme due to its role as a virulence factor in certain pathological conditions. In humans there is no case of nickel deficiency presented in professional literature, therefore the use of dietary supplements containing nickel has no rational base. Nickel compounds are known to cause skin allergies, lung fibrosis, kidney and cardiovascular system poisoning and stimulate the neoplastic transformation of cells.
Keywords: biokatalizatorji; mikroelementi; nikelj; toksičnost